Receiver Jitter Tracking Characteristics in High-Speed Source Synchronous Links - Ahmed Ragab; Yang Liu; Kangmin Hu; Patrick Chiang; Samuel Palermo (Journal of Electrical and Computer Engineering)
High-speed links which employ source synchronous clocking architectures have the ability to track correlated jitter between clock and data channels up to high frequencies. However, system timing margins are degraded by channel skew between clock and data signals and high-frequency loss. This paper describes how these key channel effects impact the jitter performance and influence the clocking architecture of high-speed source synchronous links. Tradeoffs in complexity and jitter tracking performance of common per-channel de-skew circuits are discussed, along with how band-pass filtering can be leveraged to provide additional jitter filtering at the receiver. Jitter tolerance analysis for a 10 Gb/s system shows that a near all-pass delay-locked loop (DLL) and phase-interpolator- (PI-) based de-skew performs best under low skew conditions, while, at high skew, architectures which leverage band-pass clock filtering or a phase-locked loop (PLL) for increased jitter filtering are more suitable. De-skew based on injection-locked oscillators (ILOs) offer a reduced complexity design and competitive jitter tolerance over a wide skew range.